Pengaruh Food Vlogger dan Online Customer Review Terhadap Minat Beli Ulang Pada Bakso Urat Juara Tembung - Putri, Serly; Sri Rezeki (LPPM STIE EKA PRASETYA, 2025)
Bakso Urat Juara Tembung is one of the Meatball shops that has a large number of consumers in Tembung. Apart from having several branches, Bakso Urat Juara Tembung also has social media with quite a lot of followers, making it easier to attract consumer interest with their products. However, it turns out that there are still problems regarding the Interest in Rebuying of Bakso Urat Juara Tembung. The purpose of this study is to find out and analyze the influence of food vloggers on the interest in rebuying Bakso Urat Juara Tembung. The research method used in this study is a quantitative method. The type of data used is primary data. The number of samples in the study was 96 respondents of Bakso Urat Juara Tembung. Based on the results of the study, it was obtained that partially the variable of food vloggers had a positive and significant effect on repurchase interest with a t-count value > t-table, namely 9,359 > 1,984. Partially, the online customer review variable had a positive and significant effect on repurchase interest with a t-count value > t-table, which was 13,002 > 1,984. Then simultaneously, the variables of food vlogger and online customer reviews had a positive and significant effect on repurchase interest with the result of F count 140,580, > 3.09 and the determination coefficient explaining the repurchase interest with an Adjusted R Square value of 73.8% so that the hypothesis was accepted.